2020
DOI: 10.1002/cctc.201902039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Metal‐zeolite Composite Catalysts: Determining the Environment of the Active Phase

Abstract: Metal‐zeolite composite catalysts are attracting increased attention due to their unique multifunctional properties. However, it is challenging to identify the physicochemical environment of the active phase, which is essential to improve our understanding of the structure‐performance relationships of such complex catalysts. In this work, commonly available analytical techniques (FTIR, TEM, XRD, etc.) and state‐of‐the‐art user instrumentation (XAS, SANS, e‐TEM, etc.) are reviewed with respect to their applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 209 publications
(273 reference statements)
0
34
0
Order By: Relevance
“…correspond to lineal bonded CO to Pt nanoparticles, while the bands at 1693 to 1887 cm -1 can be associated to Co adsorbed on Pt clusters. Assignation of the IR bands to Pt carbonyl species has been verified by 13 CO IR adsorption studies, where the corresponding shift to ∼50 cm -1 lower wavenumbers have been observed.…”
Section: Figurementioning
confidence: 62%
See 1 more Smart Citation
“…correspond to lineal bonded CO to Pt nanoparticles, while the bands at 1693 to 1887 cm -1 can be associated to Co adsorbed on Pt clusters. Assignation of the IR bands to Pt carbonyl species has been verified by 13 CO IR adsorption studies, where the corresponding shift to ∼50 cm -1 lower wavenumbers have been observed.…”
Section: Figurementioning
confidence: 62%
“…Compared to supported metal catalysts on conventional solid carriers (such as carbon, metal oxides, etc. ), metal species confined in zeolites, or generally speaking, in porous materials, are more difficult to characterize, especially when one needs to obtain the structural information at atomic level [13][14][15] . From a structural point of view, the geometric structure of a subnanometric metal entity (isolated atom or cluster) is directly related to its surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, EXAFS and IR spectroscopy can be complementary for the gain of global information on the metal dispersion. It is critical to perform characterizations on both the structure of porous matrix with metal species and the metal-reactant interaction for understanding the catalysis of confined metal species 121 .…”
Section: Combination Of Different Techniquesmentioning
confidence: 99%
“…The activation energy required to reach the conversion state is lowered by the catalyst via the provision of an alternative reaction pathway [8]. The choice of catalysts used in catalytic cracking is dependent on the regenerative potential, unique microporous structure, economic cost, and thermal stability [9]. The modern-day petroleum industry commonly uses zeolite as a catalyst during catalytic cracking.…”
Section: Introductionmentioning
confidence: 99%
“…The constituents of composite materials do not mix or completely homogeneous, thereby giving rise to the presence of two or more phases within the composite material [14]. The mitigation of greenhouse gases, direct conversion of methane to methanol, and linear paraffin isomerization are specific reactions in oil refining strongly associated with the use of composite catalysts [9,23,24].…”
Section: Introductionmentioning
confidence: 99%